Unaccustomed Complications of Epidurals for Labor Analgesia Insight from Five Years of Clinical Experiences- A Narrative Review - Bhattarai, Prajjwal Raj (Birat Journal of Health Sciences, 2025)
AbstractEpidural labor analgesia (ELA) has become the standard of care for pain management during childbirth. However, implementing an ELA program in settings without established policies presents challenges, including the management of unfamiliar complications. This narrative review summarizes five years of clinical experience with ELA, focusing on unaccustomed (e.g., unilateral epidural effects, CSF-cutaneous fistulas, knotting of epidural catheters, blurring of vision, and pneumocephalus). Strategies for diagnosing, managing, and preventing these complications are discussed. This review highlights the need for national level protocols and continuous medical education to address unaccustomed events associated with ELA.